Location and Number of Comparison Points of Measuring Instruments (Texas Journal of Multidisciplinary Studies, 2022)
In this article, the selection of the number of points to be compared during the comparison of measuring instruments, the determination of one of the factors most influencing the error of the measuring instruments in order to find their exact value was carried out by calculating the coefficients of the Fourier series.